The influence of online customer rating, online customer review and taglines “free shipping” on purchasing decisions at the shopee marketplace in Cikarang - Zed, Etty Zuliawati; Pupung Purnamasari; Sesri Sellina (SEAN Institute, 2024)
The purpose of this study was to analyse the effect of each independent variable: online customer rating, online customer review and